FINAL YEAR MEDICAL STUDENTS’ KNOWLEDGE, ATTITUDE AND PRACTICE OF MEDICO-LEGAL PROBLEMS: A CROSS SECTIONAL STUDY AT IBN SINA NATIONAL COLLEGE IN JEDDAH: Pharmaceutical Science-Medicine - KAMAL ZAKI, MAMDOUH; M ESTANBOLI, HANEEN; ALDUHAILIB, HASSAN; A BOSSI, ASSEL; SULTAN, INTESSAR (International Journal of Life Science and Pharma Research, 2019)
Forensic medicine encompasses various subspecialties that involve resolving legal issues using diverse techniques. Medical students should be prepared for their near future career, in particular, the challenge of facing medico-legal cases with their consequent legal responsibilities. The aim of the study was to assess final year medical students’ knowledge, attitude and practice of medico-legal problems. This crosssectional study included randomly selected 138 6th year medical students at Ibn Sina National College in Jeddah. 56 (40.6%) were male and 82 (59.4%) were female, aged 24.46±1.45 years, and 114 (82.6%) were Saudis. A pre-designed, self-answered 23-item questionnaire in English was devised by a specialist in the field and circulated though Survey-Monkey forms from November 2018 to January 2019. Most students had good knowledge (66.27%) and positive attitude (71.47%). Some had poor (14.49%) or no knowledge (19.24%), negative (15.67%), or borderline attitude (14.31%). Poor responses were the legal value of incomplete reports (28.99%), notifications of relatives before police notification (15.94%) and informed consent before photographing (21.74%). Many students (44%) had negative attitude towards their current medico-legal overall education and knowledge. Only 14.5% had been previously involved in photographic documentation. Students thought that the main sources of stress/pressure during managing medico-legal problems were the victim’s relatives (69.79%), followed by fear of legal consequences (54.17%). They also thought that the best educational stage for medico-legal training programs should be during undergraduate years (57.25%), or less frequently during residency (55.8%) or post-graduate years (46.38%). In conclusion, final year medical students were prepared for their future practice by good knowledge and positive attitude towards medico-legal problems. However, many gaps were detected between theory and practice. Therefore, we recommend medical colleges to initiate an undergraduate clinical forensic medicine training program. Moreover, residents and post graduate emergency physicians need to know their medico-legal responsibilities and to acquire technical skills to perform forensic evaluations of victims.